Intrinsic kinetics of biofilms formed under turbulent flow and low substrate concentration - M. J. Vieira (1999)
Reactor operating conditions strongly affect the behaviour of biofilm systems, namely their stability and the substrate removal. In this paper, the penetration of substrate and the activity of biofilms formed by Pseudomonas fluorescens under turbulent flow and low substrate concentrations, are studied. A first order diffusion-reaction model was applied to results of biofilm accumulation in steady and non-steady-state. The substrate consumption rate of the biofilm was calculated based on the on-line determination of the biofilm accumulated on the surface. This approach is important when the residence time or the substrate concentration on the reactor is very low. Also, the mass transfer of substrate inside the biofilm was measured for every case under study and introduced in the model. The fraction of biofilm penetrated by the substrate depends on the velocity of the fluid that contacts the biological matrix: contrary to biofilms formed at higher velocities, lower velocities give raise to non completely penetrated biofilms. This fact seems to be associated to the biofilm internal structure in terms of biomass density and compactness of the matrix. They remove more substrate per reactor volume, but are less resistant from an hydrodynamic point of view. In conclusion, biofilms formed at higher velocities in turbulent flow allow a more stable reactor operation.